Measurement and analysis of bubble pump and Einstein-Szilard single pressure absorption refrigeration system - Chan, K (2011)
The increasing demand for the domestic refrigeration system urges the development of greener form of refrigeration. The eighty-year-old single pressure absorption refrigeration system invented by Albert Einstein and Leo Szilard is attractive as it has no mechanical moving parts and can be driven by heat alone. However, the literature on either the refrigeration system or its components is scarce. The bubble pump is the crucial component of the refrigeration system, but it is poorly understood as its mass flow rate cannot be readily predicted. Two new time correlations in the mass flow rate prediction are presented to increase the accuracy when heat losses occur in the bubble pump. These time correlations are verified with the experimental results. When either the heat input or submergence ratio increases, the accuracy of the prediction increases. The percentage of error for the high heat input or submergence ratio is within ±10%. Working conditions and system dimension have a direct influence to the bubble pump performance. For instance, the bubble pump experimental results show that the mass flow rate of the bubble pump increases when either the submergence ratio or the concentration of ammonia increases. However, the performance of the bubble pump drops when the tube diameter or the system pressure increases. The Einstein refrigeration system has only been rebuilt once since it invention. In order to redesign and rebuilt a practical Einstein refrigeration system, some challenges are revealed. With the combination of the good features of the designs of Einstein and Delano, a new prototype has been rebuilt and tested. The practical results obtained from the five experimental setups are the first set of experimental result that has ever been presented. The highest cooling capacity and coefficient of performance (COP) obtained are 5 W and 0.04 respectively.